Evaluating the impact of a family violence transformational change project in a major trauma hospital: A three-year follow-up comparison study of knowledge, confidence, and family violence response skills in clinical staff - Fisher, Caroline A.; Troy, Kirsty; Rushan, Catherine; Felmingham, Kim; Withiel, Toni D. (Frontiers in Health Services, 2023)
Family violence is a significant public health issue. Healthcare systems have an important role to play in recognising and responding to current family violence experiences in their patients. However, many healthcare workers and systems remain underprepared to fulfil this role. The current study evaluated the impact of a transformational change project in family violence clinical response at a major adult trauma hospital in Australia. Clinician self-rated knowledge, confidence, and family violence clinical skills were evaluated at three years post implementation of a family violence initiative at the Royal Melbourne Hospital, Melbourne. The three years post survey results (N = 526) were compared to baseline (N = 534) using Mann Whitney U and χ2 analyses. Self-reported clinician family violence knowledge, confidence and patient screening were all significantly improved from baseline. Specific family violence skills, including knowledge of key indicators, enquiry with patients and disclosure response were also all significantly improved. The most common clinician identified barriers to working effectively in the area were similar to baseline and included the presence of a suspected perpetrator during the clinical interaction, clinicians perceiving patients would be reluctant to disclose, and time limitations. However, significantly fewer staff endorsed a lack of knowledge or supporting policies and procedures as a barrier. The findings indicate that investment in a transformational change project comprised of the establishment of response policies and clinical work-flow, broad-scale training, a clinical champions program, a secondary consultation service and links with partner organisations, was effective at improving clinician self-rated rated family violence skills, across the hospital. However, one quarter of clinicians still reported having not received any family violence training, and half endorsed having little or no confidence in their skills to identify and respond to patient family violence experiences. This indicates ongoing and sustained work is required to optimise clinician skills in responding to family violence.